Stratigraphy of the central sector of the Loncopué Trough: The Quaternary depocenter of the Huecú (Western sector of the Neuquén basin) - Rojas Vera, E.A. (2009)
The Huecú depocenter is located in the central sector of the Loncopué trough in western Neuquén. This basin is composed of volcanic, volcaniclastic, fluvial and lacustrine deposits, younger than 1.6 Ma encompassing postglacial and even historical sediments and lavas. During most of its evolution, the Huecú depocenter has constituted a small closed depression (pullapart basin) restricted to the Loncopué trough, a major extensional retroarc basin in the Central and Patagonian Andes. This basin was fed from the north since the beginning of its evolution by a series of big amalgamated post-Pliocene stratovolcanoes located in the Mandolegüe Cordillera. The basin was also filled by fissural lava flows originated in the Agrio caldera located to the east grouped in the Escorial Basalt of 1.6 to 0.8 Ma. Polygenetic volcanic products form in the region big stratovolcanoes among which the Trolón and Colorado volcanic centers were the most prominent. These centers of Pleistocene age were highly eroded by the last glacial activity that affected the region. Nearly at the end of the glacial period two fissural volcanic fields covered the Huecú depocenter corresponding to the Rankül-Lom Basalt and preglacial Tres Hermanos basalts. Finally postglacial volcanic lavas covered most of the Huecú depocenter. These were grouped in the Cerro Artillería Basalts and postglacial Tres Hermanos basalt, which have recurrently dammed the main fluvial basins in the area. The fluvial and lacustrine deposits are represented by El Huecú and Mar Pequeño Formations.